Vocabulary Learning Revolution with Jamboard in 7th grade at SMPN 1 Gandusari - Dewi, Putri Ulfa; Dian Fadhilawati; Nita Sutanti; Hesty Puspita Sari (EDUJ : English Education Journal, 2024)
This study aimed to assess the effectiveness of Jamboard in enhancing the vocabulary achievement of seventh-grade students at SMPN 1 Gandusari, particularly in describing places and understanding meanings, synonyms, and antonyms. The research employed a one-group pretest and post-test pre-experimental design involving 32 students. The methodology included three key phases: pretest, treatment, and post-test. Tests were used to gather data, and before administering the test to the participants, the test's reliability and validity were ensured through preliminary trials. Data analysis was conducted using paired sample t-tests with SPSS 25. The findings revealed a significant improvement in students' vocabulary achievement, with scores increasing from an average of 63.63 in the pretest to 92.25 in the post-test. The paired sample t-test indicated a Sig. (2-tailed) value of less than 0.05, confirming a significant difference in learning outcomes between the pretest and post-test. This suggests that Jamboard effectively improves the vocabulary of seventh-grade students at SMPN 1 Gandusari, particularly in describing places. Based on these results, it is recommended that teachers incorporate Jamboard into English language instruction to make learning more engaging. Teachers could also use Jamboard to teach other topics. Additionally, students are encouraged to regularly review vocabulary related to describing places. Future research could explore student and teacher responses to Jamboard for different subjects or compare its effectiveness with other language learning tools such as Duolingo, Baamboozle, and Beelingoapp.